1972
DOI: 10.2307/1239164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Minimum Wages Upon the Level and Composition of Agricultural Employment

Abstract: This paper investigates the effects of minimum wages on agrieultural employment in the southern U. S. The prineipal result was that the introduetion of minimum wages decreased the employment of hired and total (hired plus family) labor. Esthnates of employment reduetion of hired labor due to minimum wages are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

1974
1974
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
(7 reference statements)
2
19
1
Order By: Relevance
“…and U K. Similar models to the ones outlined be!ow which have been uscd in the U.S. can he 'cund in Griliches 1111, Schuli [ 1 9 , Wallice arid Hoover [ 1 9 ] . Rauer [ I ] , 'Tyrcitnicwicz and Schuh [lS], G x d n e r [9] and Liainos [13]. Ir, ihe il K. t h e are t!ie studies by Cowling The equations were also estimated with fixed-weight Fisher lags on the real price variables.…”
Section: Single-equation Estimation Of Input-demand Elasticitiesmentioning
confidence: 99%
“…and U K. Similar models to the ones outlined be!ow which have been uscd in the U.S. can he 'cund in Griliches 1111, Schuli [ 1 9 , Wallice arid Hoover [ 1 9 ] . Rauer [ I ] , 'Tyrcitnicwicz and Schuh [lS], G x d n e r [9] and Liainos [13]. Ir, ihe il K. t h e are t!ie studies by Cowling The equations were also estimated with fixed-weight Fisher lags on the real price variables.…”
Section: Single-equation Estimation Of Input-demand Elasticitiesmentioning
confidence: 99%
“…A very early time series study of the effects of minimum wages on employment (Lianos 1972) analyzed the effect of the federal minimum wage on farm labor and found that the minimum wage increased farm wages and decreased farm employment as expected. To minimize the bias due to unobserved geographic factors, this study focused on the south and used regional wage measures to account for geographic differences.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Behar (2004) estimated the price elasticity of demand for unskilled and semi-skilled workers in the SA manufacturing sector as -0.65 and -0.8 respectively, while Fedderke and Mariotti (2002:860) report a wage elasticity of demand estimate for the SA manufacturing sector of about -0.5. Lianos (1972) estimated the price elasticity of demand for hired farm labour in the United States (US) as -1.37, while Gardner (1972) estimated a figure for the US of -1.4.…”
Section: Demand For Farm Labour In South Africamentioning
confidence: 99%
“…A relative increase in the cost of labour motivates farmers to replace labour with machinery, machinery contractors, labour contractors or new technologies that are labour-saving. This in turn can lead to considerable unemployment if the demand for labour is very price elastic (Lianos, 1972;Conradie, 2005), and output will fall as production costs increase (Burton et al, 1970).…”
Section: Introductionmentioning
confidence: 99%